Formation basée sur la perturbation : preuve de concept par la conception et le test d’un environnement numérique de formation en radiologie médicale - Stéphanie Schot; Simon Flandin; Annie Goudeaux; Laurence Seferdjeli; Germain Poizat (Activités)
By contrast with most common training models, perturbation-based training does not consist in the transmission of established knowledge. It aims to produce a “shock” to encourage the making of new meanings and to foster the development of new actions. This study is embedded in a technological research program on training. It consists in a proof of concept within an ergonomic approach to training in the field of medical radiology. The aim of this study was to (i) operationalize and test the design principles of perturbation-based training, and to (ii) develop a training tool for medical radiology technicians. This research consisted in designing a digital training environment (DTE) and testing it with a trainer who did not participate in the design. We empirically documented (i) the discovery of the DTE by the trainer using interruptive verbalization data, and (ii) the use of DTE by the trainer using observations and self-confrontation interviews. Results revealed expected and potentially constructive perturbations regarding professional culture, but also unexpected and potentially counterproductive perturbations regarding training culture, that created obstacles to the appropriation of the DTE. We analyze three types of perturbation and conclude with propositions for the design of perturbation-based training.